The Effectiveness of Group Counselling with Cognitive Defusion Technique in Reducing Negative Thinking among Students Experiencing Parental Absence - Rahma Sri Anggraini; Ahmad Syarqawi (Journal of General Education and Humanities, 2025)
Parental absence is known to disrupt adolescents’ emotional stability and cognitive functioning, often leading to persistent Negative Thinking in school contexts. This study aimed to examine the effectiveness of group counselling services using the Cognitive Defusion technique in reducing negative thinking among students experiencing Parental Absence at SMA Negeri 1 Siantar. A quasi-experimental method with a pretest–posttest control group design was employed. Sixteen students were selected through purposive sampling and divided into two groups: an experimental group of eight students and a control group of eight students. The instrument used was a negative thinking questionnaire adapted from Charry Mae P. Cepada-Grepon. Data were analysed using the Shapiro–Wilk normality test, Levene’s homogeneity test, paired-sample t-test, and independent-sample t-test. The findings showed a significant reduction in negative thinking scores in the experimental group compared to the control group (p < 0.05). These results indicated that Cognitive Defusion was effective in helping students distance themselves from negative thoughts, interpret them more objectively, and reduce their emotional impact. The study concluded that Cognitive Defusion can serve as a valuable counselling intervention to support students experiencing parental absence. These findings also suggest implications for school counsellors in promoting students’ psychological resilience through structured mental health programs.